Novel Use of Ultrasound to Teach Reproductive System Physical Examination Skills and Pelvic Anatomy. (28th September 2017) - Parikh, Tejal; Czuzak, Maria; Bui, Naomi; Wildner, Corinna; Koch, Bryna; Leko, Elizabeth; Rappaport, William; Adhikari, Srikar; Gordon, Paul; Gura, Mike; Ellis, Susan
Abstract : Objectives: To determine whether integration of ultrasound (US) into a reproductive system examination clinical skills lab can increase confidence in palpating key reproductive structures during testicular and bimanual pelvic examinations, reduce anxiety about conducting testicular and bimanual pelvic examinations, and improve performance on multiple‐choice questions based on structure identification using US images. Methods: Second‐year medical students enrolled in the Life Cycle preclinical course participated in this cross‐sectional study. A single learning activity was developed to pair the teaching of the reproductive system physical examination with the use of US in the clinical skills lab. The evaluation of the teaching session consisted of a pre‐post analysis of student self‐reported knowledge, confidence, and anxiety. Results: The response rate for the pre survey was 82% (n = 96), and the rate for the post survey was 79% (n = 93). Students' confidence in their ability to identify reproductive system structures on US images increased from pre to post survey. Their confidence in their ability to palpate the epididymis, uterus, and ovary during a physical examination improved, and their anxiety about conducting testicular and bimanual pelvic examinations decreased. Student satisfaction with the session was high. Students' performance on multiple‐choice questions based on structure identification using US images was at 96% or higher. Conclusions: Our study findings support the integration of US into a reproductive system examination clinical skills lab. Medical students acquire competency and confidence in reproductive system physical examination skills with US integration.